Pengaruh Kualitas Pelayanan, Lokasi, Harga Dan Cita Rasa Terhadap Kepuasan Konsumen Di Cafe Mawar Desa Cinta Makmur Kecamatan Panai Hulu Kabupaten Labuhanbatu - Surya, Muhammad (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study was conducted at Cafe Mawar Desa Cinta Makmur, Panai Hulu Sub-District, Labuhanbatu, which aims to find and identify the effect of Service Quality, location, price and taste on consumer satisfaction in Cafe Mawar. This type of research is associative research. Quantitative descriptive data collection by distributing questionnaires to 50 respondents. Data collection techniques are carried out by interviews, questionnaires and documentation studies. Data analysis tools used in this study using SPSS (statistical Product Software Solusion). Analytical techniques in this study are descriptive analysis, hypothesis testing using partial significant Test (t test), simultaneous significance test (F test) and determinant coefficient test (R2). The results of this study showed that partially (t test) service quality positive and significant effect on consumer satisfaction with Thitung (2,152) > Ttable (1,67943), location positive and significant effect on consumer satisfaction with Thitung (2,351) > Ttable (1,67943), price positive and significant effect on consumer satisfaction with Thitung (2,120) > Ttable (1,67943) and taste effect on consumer satisfaction with (2,162) > Ttable (1.67943). While the results of the simultaneous Test (Test F) quality of service, location, price and taste together (simultaneous) significantly affect consumer satisfaction with Fhitung (14,185) > Ftable (2,578). Through testing coefficient determination (R Square) of 0.558 means 55.8% of the factors of consumer satisfaction at Cafe Mawar Cinta Makmur Village Panai Hulu District Labuhanbatu can be explained by the quality of service, location, price and taste. While the remaining 44.2% can be explained by other factors that are not studied in this study.